The post-pandemic library handbook - Todaro, Julie 1950- (Rowman & Littlefield Publishers, 2022)
"Here's your library's guide for reopening, reengineering and redesigning library facilities, resources, services and staff for the post-pandemic era"--Provided by publisher.